Perbandingan Fikih Tentang Konsep Harta dalam Islam (Studi Komparatif Empat Mazhab dan Aplikasinya pada Harta Kontemporer) - Asnan Purba; Ayi Yunus Rusyana; Fauzan Januri (SPT. haria Journal and Education Center Publishing, 2026)
This study examines the concept of property (al māl) through the lens of the four schools of Islamic jurisprudence Hanafi, Maliki, Shafi'i, and Hanbali as a legal discipline oriented toward determining the validity or invalidity (al ḥukm) of a practice within mu'āmalah māliyyah. Unlike exegetical studies preoccupied with the meaning of verses, this article concentrates on the formulation of rulings (al aḥkām) and legal maxims (al qawāʻid al fiqhiyyah) concerning the definition, criteria, and legal consequences of property. The research employs a qualitative normative legal approach grounded in a literature review, selecting opinions according to the mu'tabar or al muʻtamad (authoritative) criterion within each school. The data are analysed through comparative (muqāranah) and conceptual techniques by constructing five evaluative markers: taʻyīn, qīmah, qabḍ, manfaʻah mubāḥah, and ḍamān. The findings reveal that the four schools differ in emphasis, whose roots can be traced to their respective uṣūl al fiqh methodologies, yet such differences can be woven into a single operational evaluative framework applicable to various contemporary forms of property, ranging from digital assets and cryptocurrencies to intellectual property rights and modern Islamic financial instruments. The study concludes that the classical fiqh framework remains relevant and flexible as long as its foundational maxims are applied consistently and supported by the rulings of contemporary fatwa institutions.